What is the best empiric antibiotic treatment regimen in adults hospitalized with community‐acquired pneumonia?. Issue 12 (December 2017) - Gaba, Payal; Johansing, Patrick
Abstract : EVIDENCE‐BASED ANSWER : Fluoroquinolone monotherapy or a beta‐lactam combined with a macrolide are both associated with lower 30‐day mortality rates than beta‐lactam monotherapy in adults hospitalized with communityacquired pneumonia (CAP) (SOR: B, systematic review of observational studies and RCTs). Macrolide use is associated with reduced mortality compared with nonmacrolide therapies in critically ill adults (SOR: B, systematic review of observational studies). Either a respiratory fluoroquinolone or a beta‐lactam plus macrolide should be used for hospitalized patients outside of the intensive care unit (ICU), and a betalactam plus either a fluoroquinolone or azithromycin should be used for patients in an ICU (SOR: C, expert opinion).